Potential and limitations of scale resolved simulations for ship hydrodynamics applications. Issue 2 (4th May 2019) - Kornev, Nikolai; Shevchuk, Ivan; Abbas, Nawar; Anschau, Pascal; Samarbakhsh, Sina
ABSTRACT: The paper gives an overview of experience gathered by the authors in development and application of hybrid URANS/LES methods for the solution of ship hydrodynamic problems. Difficulties arising at the interface between URANS and LES are discussed and illustrated for a channel flow benchmark. A hybrid model developed by the authors is described. It was shown that pure LES has advantages over hybrid models provided a sufficient resolution can be attained for a given Re number. Advantages of hybrid models over RANS-based ones is demonstrated for the determination of wake parameters behind models of full bottomed ships JBC and KVLCC2. Difficulties with prediction of the ship resistance by hybrid methods are discussed.